Obesity increases cardiovascular mortality in patients with HFmrEF - Liu, Zhican; Peng, Yiqun; Zhao, Wenjiao; Zhu, Yunlong; Wu, Mingxin; Huang, Haobo; Peng, Ke; Zhang, Lingling; Chen, Sihao; Peng, Xin; Li, Na; Zhang, Hui; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background： High body mass index increases the risk of heart failure morbidity and mortality. It is unclear whether a high body mass index is associated with prognosis in patients with heart failure with mildly reduced left ventricular ejection fraction (HFmrEF). We retrospectively analyzed the effect of a high body mass index on the prognosis of patients with HFmrEF. Methods： We investigated the association between body mass index and cardiovascular death (death from any cardiovascular mechanism) in 1,691 HFmrEF patients (mean age, 68 years; 35% female) in Xiangtan Central Hospital. Using Cox proportional hazards models, body mass index was assessed as a continuous and a categorical variable. Results: Cardiovascular death occurred in 133 patients (82 males and 51 females) after one year of follow-up. After adjustment for established risk factors, there was a 7.5% increase in the risk of cardiovascular death for females for each increment of 1 in BMI. In contrast, changes in male body mass index were not significantly associated with cardiovascular death (P=0.097). Obese subjects had a 1.8-fold increased risk of cardiovascular death compared with subjects with a normal body mass index. The hazard ratio for females was 2.163 (95% confidence interval: 1.150–4.066). Obesity was not significantly associated with cardiovascular death in males (P=0.085). Conclusions: An increased body mass index is associated with an increased risk of cardiovascular death in patients with HFmrEF; however, this risk was mainly associated with female patients with HFmrEF and less with male patients with HFmrEF.